Corruption and Government Intervention on Bank Risk-Taking: Cases of Asian Countries - Nurhidayat, Rizky Maulana; Rokhim, Rofikoh (Department of Management, Faculty of Economics and Business, Universitas Negeri Semarang, 2018)
This paper aims to addresses the impact of corruption, anti-corruption commission, and government intervention on bank’s risk-taking using banks in Asian Countries such as Indonesia, Malaysia, Thailand, and South of Korea during the period 1995-2016. This paper uses corruption variable, bank-specific variables, macroeconomic variables, dummy variables and interaction variable to estimate bank’s risk-taking variable. Using data from 76 banks in Indonesia, Malaysia, Thailand and South Korea over 21 years, this research finds consistent evidence that higher level of corruption and government intervention in crisis-situation will increase the risk-taking behaviour of banks. In the other hand, bank risk-taking behaviour minimized by the existence of anti-corruption commission. In addition, this paper also finds that government intervention amplifies corruption’s effect on bank’s risk-taking behaviour because of strong signs of moral hazard and weaknesses in the governance and supervision.